Reliability and criterion‐related validity testing (construct) of the Endotracheal Suction Assessment Tool (ESAT©). Issue 9 (May 2018) - Davies, Kylie; Bulsara, Max K.; Ramelet, Anne‐Sylvie; Monterosso, Leanne
Abstract : Aims and objectives: To establish criterion‐related construct validity and test–retest reliability for the Endotracheal Suction Assessment Tool© (ESAT©). Background: Endotracheal tube suction performed in children can significantly affect clinical stability. Previously identified clinical indicators for endotracheal tube suction were used as criteria when designing the ESAT©. Content validity was reported previously. The final stages of psychometric testing are presented. Design: Observational testing was used to measure construct validity and determine whether the ESAT© could guide "inexperienced" paediatric intensive care nurses' decision‐making regarding endotracheal tube suction. Test–retest reliability of the ESAT© was performed at two time points. Methods: The researchers and paediatric intensive care nurse "experts" developed 10 hypothetical clinical scenarios with predetermined endotracheal tube suction outcomes. "Experienced" ( n  = 12) and "inexperienced" ( n  = 14) paediatric intensive care nurses were presented with the scenarios and the ESAT© guiding decision‐making about whether to perform endotracheal tube suction for each scenario. Outcomes were compared with those predetermined by the "experts" ( n  = 9). Test–retest reliability of the ESAT© was measured at two consecutive time points (4 weeks apart) with "experienced" and "inexperienced" paediatric intensive care nurses using the same scenarios and tool to guide decision‐making. Results: No differences were observed between endotracheal tube suction decisions made by "experts" ( n  = 9), "inexperienced" ( n  = 14) and "experienced" ( n  = 12) nurses confirming the tool's construct validity. No differences were observed between groups for endotracheal tube suction decisions at T1 and T2. Conclusion: Criterion‐related construct validity and test–retest reliability of the ESAT© were demonstrated. Further testing is recommended to confirm reliability in the clinical setting with the "inexperienced" nurse to guide decision‐making related to endotracheal tube suction. Relevance to clinical practice: The ESAT© is the first validated tool to systematically guide endotracheal nursing practice for the "inexperienced" nurse.